2022
DOI: 10.1155/2022/2366632
|View full text |Cite|
|
Sign up to set email alerts
|

Electronic Health Record Monitoring System and Data Security Using Blockchain Technology

Abstract: Bangladesh should have owned a decentralized medical record server. We face a lot of issues, such as doctor’s appointments, report organization in one spot, and report follow-ups. People now bring a large number of papers to the doctor’s chamber. They carry prescriptions, reports, and X-ray files, among other things. It complicates everyone’s life as a result. All of the reports must be reviewed by doctors on a regular basis. It is difficult to read old reports on a regular basis, and patients do not receive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 18 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Then, using the discovered vest node and the same principle to identify multiple vest accounts, the author can quickly identify multiple vest accounts. Assigning credibility levels to other nodes using the Sybil Rank algorithm [ 4 ] involves using the random walk algorithm. According to the standardized and degree value findings, the nodes with a lower credibility value are placed at the bottom of the list.…”
Section: Graph Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, using the discovered vest node and the same principle to identify multiple vest accounts, the author can quickly identify multiple vest accounts. Assigning credibility levels to other nodes using the Sybil Rank algorithm [ 4 ] involves using the random walk algorithm. According to the standardized and degree value findings, the nodes with a lower credibility value are placed at the bottom of the list.…”
Section: Graph Algorithmmentioning
confidence: 99%
“…Among them, abnormal users are one of the standard methods criminals use to attack healthcare social networks. For example, merchants distort product value orientation for commercial interests [ 1 3 ]; criminals use multiple vests to deceive Internet users, steal information, or even online fraud [ 4 6 ]. According to statistics, the types of abnormal users also show a variety of forms due to different types of healthcare social networks.…”
Section: Introductionmentioning
confidence: 99%
“…We compiled findings on the various privacy-preserving EHR approaches and evaluated their effectiveness. The data access times and storage costs are relatively high compared to the other existing approaches but considering the data privacy, security, data integrity and interoperability factors, the use of blockchain could be a significant approach for healthcare systems (Akhter Md Hasib et al, 2022;Chelladurai and Pandian, 2022;Mantey et al, 202;Mahajan et al, 2022;Watford et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They are the on-premise approach (Loukides et al, 2014;Fan et al, 2018;Guo et al, 2018;Xia et al, 2017), the cloud-based approach (Tu et al, 2010;Hamid et al, 2017;Li et al, 2013;Liu et al, 2015) and the blockchain-based approach (Akhter Md Hasib et al, 2022;Chelladurai and Pandian, 2022;Mantey et al, 2022;Mahajan et al, 2022).…”
Section: Privacy Levelsmentioning
confidence: 99%
“…The present paper presents a thorough examination of the aspects and issues concerning the use of blockchains in EHRs. For example, Alla et al (2018) [60] indicated that the patient could lose control across the prevailing EHRs in the course of live actions, despite the fact that the service provider constantly retains the principal stewardship.…”
Section: Electronic Health Recordmentioning
confidence: 99%